Efficiency of National Taskforce for Combating the Coronavirus (COVID-19) Protocol using real-time PCR testing in health facilities over a period of 8-weeks - Fahad Al Qooz; Khalid Behzad; Nayef Louri; Khalid Al-Khalifa (Elsevier, 2021)
Background: Following declaration of Corona Virus Disease 19 (COVID-19) as a global outbreak by the WHO with recommendation to do nasopharyngeal swabs for diagnosis. Many countries started to take different measures of precautions. The Kingdom of Bahrain COVID team (National Taskforce for Combating the Coronavirus) has introduced different protocols for different categories. Objective: The aim of this study is to; determine the efficiency of the recent National Taskforce for Combating the Coronavirus (COVID-19) Protocol 5-day nasopharyngeal swab from diagnosis; by evaluating the period of time needed for a patient to retain a negative polymerase chain reaction result and to determine the number of patients who failed to retain a negative result. In addition to, evaluating the cycle threshold values of persistent positive and its relation to current evidence in literature. This study also aims to determine the number of patients that needed urgent medical care [i.e. shifting to an intensive care unit (ICU) facility] in that time frame. Materials & methods: Data were collected from the daily index master sheets present in the facility from medical database systems; ALCARE by Royal Medical Services and ORACLE Reports by iSEHA. Search engines used were PubMed/MEDLINE, Oxford Academic Database, Cochrane Database system. The duration of study was from 1-July 2020 to 31-August 2020. Results: The sample included 7196 male patients from ages 18-65 years. Median age was 36. Out of 7196 patients, 3506 retained a negative result on 5th day from diagnosis, 1594 retained a negative result on 7th day from diagnosis, and 1343 retained negative result on 9th day from diagnosis. While 618 patients failed to retain a negative result. Conclusion: This study estimated the efficiency of testing protocol based on the current prevalence state of COVID-19. They found that the current protocol was not enough for the clinical data. In addition, 7-day nasopharyngeal swab was an effective testing method. Among the patients with Ct value >24, negative infected persons should be paid close attention.